Albisporachelin, a New Hydroxamate Type Siderophore from the Deep Ocean Sediment-Derived Actinomycete Amycolatopsis albispora WP1T - Qihao Wu; Robert W. Deering; Gaiyun Zhang; Bixia Wang; Xin Li; Jiadong Sun; Jianwei Chen; Huawei Zhang; David C. Rowley; Hong Wang (Marine Drugs, 2018)
Marine actinobacteria continue to be a rich source for the discovery of structurally diverse secondary metabolites. Here we present a new hydroxymate siderophore produced by Amycolatopsis albispora, a recently described species of this less explored actinomycete genus. Strain WP1T was isolated from sediments collected at −2945 m in the Indian Ocean. The new siderophore, designated albisporachelin, was isolated from iron depleted culture broths and the structure was established by 1D and 2D NMR and MS/MS experiments, and application of a modified Marfey’s method. Albisporachelin is composed of one N-methylated-formylated/hydroxylated l-ornithine (N-Me-fh-l-Orn), one l-serine (l-Ser), one formylated/hydroxylated l-ornithine (fh-l-Orn) and a cyclo-N-methylated-hydroxylated l-ornithine (cyclo-N-Me-h-l-Orn).